The Sopranos sessions - Seitz, Matt Zoller 1968-; Sepinwall, Alan (Abrams Press, 2019)
To celebrate the 20th anniversary of The Sopranos' debut, Sepinwall and Seitz have reunited to produce The Sopranos Sessions, a collection of recaps, conversations, and critical essays covering every episode. Featuring a series of new long-form interviews with series creator David Chase, as well as selections from the authors' archival writing on the series, The Sopranos Sessions explores the show's artistry, themes, and legacy, examining its portrayal of Italian Americans, its graphic depictions of violence, and its deep connections to other cinematic and television classics
Keywords: The Sopranos -- Fernsehsendung; Chase, David / 1945 August 22-; Gandolfini, James; Sopranos (Television program); Television programs / United States; Television programs; United States